Investigating the Relationship between the Theoretical Layer Thickness of the Graphite Content of Lubricant and the Kudo’s Friction Number in the Case of Forged Parts - Ferenc Tancsics (New Ideas Concerning Science and Technology Vol. 11, 2021)
In case of numerical analysis of forged parts, it is important to specify the friction coefficient characterizing the lubrication conditions. In our paper we present a combined method of a known SU (Simple Upsetting) deformation with EDS (Energy Dispersive Spectroscopy), which shows the relationship between the Kudo’s friction number and the theoretical layer thickness of the graphite film covering the sink cavity. The tests were accomplished considering the solids content of non-synthetically produced lubricant concentrates diluted to varying degrees. The significance of this relationship is shown by the fact that we also found a link between the layer thickness and the average particle size distribution, which allows the thickness of the graphite layer sprayed onto the cavity surface to be reduced.